Kajian Sifat Kimia dan Organoleptik Brownies Pisang Tongka Langit - Erynola Moniharapon; Priscillia Picauly; Leonorang Lelmalaya (Universitas Pattimura, 2018)
This research was aimed to determine the effects of substitution of tongka langit banana flour on the chemical (moisture, protein, fiber, total sugar) and organoleptic (taste, texture, colour, overall likeness) properties of the steamed brownies. A completely randomized experimental design with four-level treatment. The ratio of banana flour and wheat flour. i.e.: (0%:100%), (25%:75%), (50%:50%), and (75%:25%). The result showed that ratio (25%:75%) was determined as the best ratio to produce brownies with the best chemical and sensory properties.